Hubungan Dukungan Keluarga dengan Kualitas Hidup Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa: The Relationship Between Family Support and Quality of Life in Chronic Kidney Failure Patients Undergoing Hemodialysis - Athiqoh Nihlatun Noor; Feri Catur Yuliani; Dwi Puji Susanti (Jurnal Keperawatan Berbudaya Sehat, 2026)
The number of chronic kidney failure cases increases every year, and hemodialysis is one of the therapies that is highly sought after by the public. Hemodialysis treatment can cause psychological distress and a decline in quality of life for patients. Family, as the closest people, plays an important role in improving the patient's mental state during hemodialysis treatment. The research aims to determine the relationship between family support and the quality of life of chronic kidney failure patients undergoing hemodialysis at Pati Islamic Hospital. The research type is cross-sectional. The population consists of all chronic kidney failure patients undergoing hemodialysis, with a sample size of 48 individuals selected thru purposive sampling. The research instruments were the Perceived Social Support - Family (PSS-Fa) survey and the Kidney Disease Quality of Life (KDQOL) questionnaire. The analysis used the Spearman rank test with a significance level of 5%. The results of the study showed that the majority of respondents had a low quality of life (47.9%) and strong family support (52.1%). Statistical analysis showed a p-value of 0.369 (p > 0.05) and a correlation coefficient of r = 0.132. Conclusion: There is no significant relationship between family support and the quality of life of chronic kidney failure patients undergoing hemodialysis at Pati Islamic Hospital.